The changing roles of the post-transitional economic elite in Poland - Krzysztof Jasiecki (Journal for East European Management Studies, 2008)
The study characterised evolution of the role of a new economic elite in Poland using the three-elite-generations metaphor: breakthrough elite, transition elite and consolidation elite. Describing this evolution in terms of the neoliberal modernisation paradigm, 'elitist paradigm' and transformation theory is insufficient for a theoretical reconstruction of changes occurring in states which, like Poland, are at the stage of development combining characteristics of post-communist, neoliberal and globalised capitalist societies. Other concepts are also useful, such as globalisation theory, world-systems theory or the varieties of capitalism approach that provide a different conceptual framework for the role of economic elites. – – Die Studie zeichnet die Entwicklung der Rolle der neuen Wirtschaftselite in Polen nach und bedient sich dabei einer Metapher von drei Elitegenerationen: die 'Durchbruch-Elite', die 'Elite des Übergangs' und die 'konsolidierte Elite'. Eine Beschreibung dieser Entwicklung im Rahmen des neoliberalen Modernisierungsparadigmas, des 'Elite Paradigmas' oder der Transformationstheorie ist ungenügend für die theoretische Rekonstruktion der Veränderungen, da sich Polen in einem Entwicklungsstadium befindet, das von Post-Kommunismus, Neoliberalismus und Globalisierung gekennzeichnet ist. Daher wird auf andere theoretische Konzepte zurückgegriffen: Globalisierungstheorie, die Theorie der Welt-Systeme oder die Varieties-of- Capitalism.
Keywords: 650; Economic elite; Poland; three-elite-generations metaphor; breakthrough elite; transition elite; consolidation elite; theoretical reconstruction; post-communist societies